1997
DOI: 10.1083/jcb.139.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Large Plasma Membrane Disruptions Are Rapidly Resealed by Ca2+-dependent Vesicle–Vesicle Fusion Events

Abstract: A microneedle puncture of the fibroblast or sea urchin egg surface rapidly evokes a localized exocytotic reaction that may be required for the rapid resealing that follows this breach in plasma membrane integrity (Steinhardt, R.A,. G. Bi, and J.M. Alderton. 1994. Science (Wash. DC). 263:390–393). How this exocytotic reaction facilitates the resealing process is unknown. We found that starfish oocytes and sea urchin eggs rapidly reseal much larger disruptions than those produced with a microneedle. When an ∼40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
252
1
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 269 publications
(260 citation statements)
references
References 52 publications
6
252
1
1
Order By: Relevance
“…NIH 3T3 fibroblasts were harvested by trypsinization from logarithmic-phase cultures. Eggs were obtained from Strongylocentrotus purpuratus (Marinus, Long Beach, CA) as described (6) and used in experiments within 4 h. Artificial seawater was prepared, with or without a 10 mM CaCl 2 addition, as described (6). Primary cultures of hippocampal neuron cultures were prepared as described (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NIH 3T3 fibroblasts were harvested by trypsinization from logarithmic-phase cultures. Eggs were obtained from Strongylocentrotus purpuratus (Marinus, Long Beach, CA) as described (6) and used in experiments within 4 h. Artificial seawater was prepared, with or without a 10 mM CaCl 2 addition, as described (6). Primary cultures of hippocampal neuron cultures were prepared as described (13).…”
Section: Methodsmentioning
confidence: 99%
“…The principal function proposed for this extracellular Ca 2ϩ is as signal-triggering homotypic and heterotypic membrane fusion responses. Thus, Ca 2ϩ -dependent exocytotic (cytoplasmic vesicle-plasma membrane) and homotypic (vesicle-vesicle) fusion events have clearly been demonstrated to correlate spatially, temporally, and quantitatively with the resealing response in fibroblasts and eggs (4)(5)(6). If these cytoplasmic membrane-dependent fusion events are required for, and are not simply correlates of, rapid resealing, then a simple prediction follows: a cell lacking cytoplasmic membrane (endomembrane) will be incapable of rapid resealing.…”
mentioning
confidence: 99%
“…The protective mechanism is calcium-activated membrane sealing (15). When the membrane is broken, the influx of extracellular calcium ions triggers fusion of intracellular vesicles at the site of injury (15,16). The added vesicle membranes plug and fuse with the injured membrane so that embryo integrity is maintained.…”
Section: Protective Strategies Independent Of Developmental Programsmentioning
confidence: 99%
“…Embryologists make use of this whenever they microinject eggs or embryos; the cells survive, and the embryos develop normally. The protective mechanism is calcium-activated membrane sealing (15). When the membrane is broken, the influx of extracellular calcium ions triggers fusion of intracellular vesicles at the site of injury (15,16).…”
Section: Protective Strategies Independent Of Developmental Programsmentioning
confidence: 99%
“…Third, increased PMO brought about by either cholesterol enrichment of the plasma membrane or exposure to a membrane ordering agent results in an increase in mechanical shear-induced plasma membrane wounding (Clarke and McNeil 1992;Clarke et al 1995). It is interesting to note that the cellular processes required for membrane resealing of a plasma membrane wound (i.e., a calcium-dependent mobilization of an intracellular membrane pool that fuses with the plasma membrane at the site of the membrane wound) (Miyake and McNeil 1995;Terasaki et al 1997) have been shown to be similar to those associated with synaptic vesicle fusion during neuronal transmission (Steinhardt et al 1994). These data suggest that conditions that inhibit membrane wound resealing and hence increase susceptibility to mechanically induced plasma membrane wounding (i.e., increased PMO) may also inhibit synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%